Bernini : the sculptor of the Roman Baroque - Wittkower, Rudolf; Bernini, Gian Lorenzo, 1598-1680.; Guidolotti, Pino.; Wittkower, Rudolf; Phaidon Press (London : Phaidon Press, 1997)
"Gian Lorenzo Bernini was the greatest and most influential sculptor of his age. Endlessly inventive and gifted with extraordinary technical skill, he virtually created the Baroque style. In his religious sculptures he excelled at capturing movement and extreme emotion, uniting figures with their setting to create a single conception of overwhelming intensity that perfectly expressed the fervour of Counter-Reformation Rome. Intensity and drama also characterize his mythological groups, his remarkable portraits and his world-famous Roman fountains. Rudolf Wittkowers classic monograph and catalogue raisonne has remained the standard work on Bernini ever since its first publication in 1955. The concise but masterly survey provides an authoritative introduction to all aspects of Berninis sculpture, while the full catalogue gives detailed, scholarly and up to date information on his complete oeuvre. This is the one indispensable book on Bernini for all students, scholars and art-lovers"--Publisher.
Early works and Borghese patronage --Religious imagery --Portrait busts --Work in St. Peter's and the Vatican --The Cornaro Chapel, other chapels, churches, and the Baroque stage --Fountains and monuments --Bernini and his period. The Organization of the studio. Theory and practice.
"This edition is based on the Italian edition published under licence in 1990 by Electa"--Title page verso.
Previous editions. have title: Gian Lorenzo Bernini: the sculptor of the Roman Baroque.
Includes bibliographical references (pages 312-314) and indexes.
Keywords: Bernini, Gian Lorenzo, -- 1598-1680.; Sculpture, Baroque -- Italy -- Rome; Sculpture baroque -- Italie -- Rome